The association of gut microbiota and complications in gastrointestinal-cancer therapies - Tourelle, Kevin M.; Boutin, Sébastien; Weigand, Markus A.; Schmitt, Felix (Biomedicines, 2021)
The therapy of gastrointestinal carcinomas includes surgery, chemo- or immunotherapy, and radiation with diverse complications such as surgical-site infection and enteritis. In recent years, the microbiome’s influence on different diseases and complications has been studied in more detail using methods such as next-generation sequencing. Due to the relatively simple collectivisation, the gut microbiome is the best-studied so far. While certain bacteria are sometimes associated with one particular complication, it is often just the loss of alpha diversity linked together. Among others, a strong influence of Fusobacterium nucleatum on the effectiveness of chemotherapies is demonstrated. External factors such as diet or specific medications can also predispose to dysbiosis and lead to complications. In addition, there are attempts to treat developed dysbiosis, such as faecal microbiota transplant or probiotics. In the future, the underlying microbiome should be investigated in more detail for a better understanding of the precipitating factors of a complication with specific therapeutic options.
Gesehen am 24.11.2021